2010
DOI: 10.1007/s10856-010-4061-1
|View full text |Cite
|
Sign up to set email alerts
|

Initial biocompatibility and enhanced osteoblast response of Si doping in a porous BCP bone graft substitute

Abstract: Granular shape biphasic calcium phosphate (BCP) bone grafts with and without doping of silicon cations were evaluated in regards to biocompatibility and MG-63 cellular response. To do this we studied Cellular cytotoxicity, cellular adhesion and spreading behavior and cellular differentiation with alizarin red S staining. Gene expression in MG-63 cells on the implanted bone substitutes was also examined at different time points using RT-PCR. In comparison, the Si-doped BCP granule showed more cellular viability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…MG63 cell line has been widely used to validate the biocompatibility in terms of cell proliferation and activity . Cells seeded onto 10%‐Si‐β‐TCP responded better than cells deposited on the β‐TCP pure material as shown in Figure .…”
Section: Discussionmentioning
confidence: 99%
“…MG63 cell line has been widely used to validate the biocompatibility in terms of cell proliferation and activity . Cells seeded onto 10%‐Si‐β‐TCP responded better than cells deposited on the β‐TCP pure material as shown in Figure .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been demonstrated that the incorporation of silicon into biocompatible materials can influence the cellular response at the bone-implant interface and thus affects bone formation (14,15).…”
Section: Original Articlementioning
confidence: 99%
“…The incorporation of specific doping elements such as phosphate and calcium is known to positively influence bone growth and cell differentiation (2,(5)(6)(7)(8). Moreover, silicon is known to play a primary role in the calcification of bone matrix, skeletal tissue development and bone metabolism (12,14,15).…”
Section: Mineralization Potential Studymentioning
confidence: 99%
“…Osteoblasts do not divide. They give rise to osteocytes, remain as osteoblasts, or return to the state of osteoprogenitor cells from which they derived (7,8,9). An osteoblast becomes an osteocyte when the cell is encased by osteoid matrix that it synthesizes itself.…”
Section: Composition Structure and Function Of Subchondral Bonementioning
confidence: 99%
“…The elastic moduli present a slight decrease after 12 weeks of degradation from 3.4 to 2.9 MPa (Table 3-6). (8) Where k is the intrinsic permeability, t the specimen thickness, A the cross-sectional area, Q is the volumetric flow rate, ∆p is the pressure difference across the sample and µ the dynamic fluid viscosity (deionized water at 10 -3 Pa). All the samples were immersed in PBS solution during 48 hours before testing.…”
Section: Mechanical Propertiesmentioning
confidence: 99%